Article Comparative Analysis of Rural Tourism Development Models: Lessons for Uzbekistan From Global Best Practices - Ruziyeva, Makhbuba (Research Parks Publishing LLC, 2025)
Rural tourism is rapidly gaining recognition worldwide as a catalyst for sustainable regional development, especially in countries seeking to diversify their economies and breathe new life into rural communities. This paper presents a comparative analysis of rural tourism development strategies implemented in China, Turkey, Russia, Kazakhstan, and several Southeast Asian nations, each of which has crafted innovative, context-sensitive models to promote tourism beyond urban centers. These countries demonstrate how effective rural tourism is not the result of isolated projects, but of well-integrated policies that connect culture, nature, economy, and community. This study synthesizes these global experiences into a set of practical, adaptable lessons for Uzbekistan, where rural regions are rich in heritage, crafts, and landscapes, yet remain underutilized in the national tourism agenda. Drawing on qualitative comparative methodology and policy evaluation tools, the article identifies key enablers of rural tourism success: state leadership, inclusive planning, financial incentives, community engagement, and diversified tourism offerings.